Method of manufacturing a lyophilized allograft bone - V. B. Khvatov; A. V. Svishchev; A. Yu. Vaza; N. V. Borovkova; A. S. Mironov; D. Yu. Pokhitonov; Yu. V. Andreev (Трансплантология (Москва))
The article describes a lyophilized sterile allograft made of bone tissue, and its implementation as a medical device in the practice of reconstructive surgery.Possessing an osteoconductive effect, the graft helps to restore the structure of a damaged bone, and accelerates the regeneration of bone defects. According to the RF Government Regulation No. 1416 of 27.12.2012, the product has to pass the authorization procedure including the conduct of specific technical, toxicological, and clinical trials to be certified by Roszdravnadzor for clinical use.